Konservasi Tanaman Obat Keluarga Unggulan Sebagai Bahan Jamu Tradisional - Fitria Alfiyah Hastuari; Anis Sufanniyah; Anisa Rahmawati Dewi; Eka Febriana Maghfiroh; Setiyo Prajoko (Jurnal Pemberdayaan Masyarakat, 2023)
The potential for very diverse biological riches such as superior Family Medicinal Plants (TOGA) has great potential. For this reason, it is necessary to organize a program so that its potential can benefit the local community. This service aims to empower Family Medicinal Plants through the conservation of superior Family Medicinal Plants in Tempurejo Village, Tempuran District, Magelang Regency as ingredients for traditional herbal medicine using the Participatory Rural Appraisal (PRA) method. The method used in this service begins with Focus Group Discussions (FGD), socialization, planting, marketing and training carried out in July – December 2023. The result of this service is that there is an increase in the community's understanding of Family Medicinal Plants after the implementation of the program from 50% to 95% resulting in an increase of 45%. Apart from public understanding, the increase in soft skills in the Ormawa HIMAPBIO PPK team can be seen from the results of the team's soft skills measurements which are carried out every month. Through this service, community income has also been significantly increased as seen from the sale of the results of the development of processed Family Medicinal Plants which are processed into traditional herbal medicine and instant herbal products.